1D and 3D co-simulation and self-adaptive position control of electrostatic levitation in China’s Space Station - Peng Zhang; Yang Zhang; Zile Wang; Yang Wang; Mao Li; Ran Niu; Li Liang; Wenju Yang; Ming Gao; Hongen Zhong; Xuzhi Li; Jianding Yu (npj Microgravity, 2022)
Abstract The greatest challenge of electrostatic levitation for containerless material processing is the stable control of charged material during heating. Recently, high-precision self-adaptive control of electrostatic levitation has been achieved in China’s Space Station. Based on the 1D and 3D co-simulation analysis, an optimal scheduling of control strategies of sample release and retrieval in space is developed. Both simulation results and on-orbit experiments demonstrated that the inversion of surface charge is responsible for the heating induced material instability. On-orbit experiments indicated that under laser illuminations, the net surface charge of metal Zr changed from positive to negative at 900 K and from negative to positive at 1300 K. The possible physical mechanism of the charge inversion of heated material is discussed.